What Is The Association Between Pedal Access Intervention And Radiologically Measured Wound Healing Progression In Diabetic Foot Ulcers? : A Systematic Review - Haekal Mahargias; Febrina Mayasari Gunawan; Mutiara Amalia (International Medical Journal Corp. Ltd, 2026)
Introduction: Diabetic foot ulcers (DFUs) represent a severe complication of diabetes, with peripheral artery disease (PAD) being a major contributor to poor healing and limb loss. Pedal access interventions, which target the small arteries of the foot, have emerged as a key revascularization strategy. However, the specific association between these procedures and radiologically measured wound healing progression requires systematic evaluation. This systematic review aims to synthesize the existing evidence on the association between pedal access interventions and radiologically assessed wound healing outcomes in patients with DFUs. Methods: A systematic review was conducted following a pre-defined protocol. We screened studies based on abstracts for inclusion criteria focusing on: (1) patients with diabetic foot ulcers, (2) pedal access interventions (angioplasty, stenting, bypass), (3) outcomes including radiologically measured wound healing, and (4) appropriate study designs (e.g., cohort studies, RCTs). Data were extracted on study characteristics, patient populations, intervention details, radiological assessment methods, wound healing outcomes, and the association between them. Results: From the screening of a large body of literature, data were extracted from numerous studies, many of which were observational cohorts. The patient populations were predominantly older males with long-standing diabetes and severe PAD. Pedal access interventions primarily involved endovascular techniques, such as angioplasty of tibial and pedal arteries, with some studies focusing on angiosome-guided or pedal arch revascularization (PAR). Radiological assessment methods varied, including duplex ultrasound (e.g., pedal acceleration time [PAT]), digital subtraction angiography (e.g., pedal arch patency), and plain radiographs (e.g., MAC scores). The synthesized evidence demonstrates a strong and consistent association between successful pedal access intervention and improved wound healing. Key findings show that a complete pedal arch (CPA) post-intervention is significantly associated with higher healing rates (e.g., 93.3% vs. 52.6% for an absent arch, p=0.003), shorter healing times (e.g., 3.5 vs. 5.7 months, p<0.001), and superior limb salvage (e.g., 100% vs. 68.4% at 1-year, p<0.001) (Troisi et al., 2018; Ismail et al., 2020). Similarly, successful PAR was associated with an 86.7% healing rate compared to 59.1% in unsuccessful cases (P=0.007) and dramatically lower major amputation rates (5.1% vs. 40.9%, p≤0.001) (Shahat et al., 2024; Jung et al., 2019). Angiosome-targeted revascularization also demonstrated superior healing outcomes compared to indirect revascularization (HR 1.97; 95% CI, 1.34-2.90) (Khor & Price, 2017; Söderström et al., 2013). Furthermore, novel non-invasive markers like PAT showed strong predictive value for wound healing (Sommerset et al., 2020; Karmy-Jones et al., 2024). Discussion: The findings robustly support the critical importance of restoring direct, pulsatile blood flow to the foot, specifically through the pedal arch and its branches, to facilitate DFU healing. The pedal arch acts as the crucial final vascular circuit, and its patency is a key determinant of healing and limb salvage. The discussion highlights that the quality of the revascularization outcome, particularly the establishment of a CPA, may be more important than the specific revascularization technique used. The integration of advanced radiological assessments like PAT offers a promising, non-invasive tool for patient selection and monitoring. Despite the strength of these associations, significant heterogeneity in study design, outcome measures, and radiological protocols exists, underscoring the need for more standardized approaches in future research. Conclusion: There is a definitive and positive association between successful pedal access intervention and radiologically measured wound healing progression in diabetic foot ulcers. Achieving a complete pedal arch and successful pedal arch revascularization are powerful predictors of superior outcomes, including faster healing, higher healing rates, and reduced amputation risk. These findings advocate for revascularization strategies that prioritize direct flow to the foot and the use of objective, non-invasive imaging to guide management.